The teaching competencies required for the Arabic language teachers for the fourth grade in the directorate of the southern Ghour - AlKhleifat, Ali Salameh Dawod (Journal of Educational and Psychological Sciences, 2020)
This study aimed at identifying the level of teaching competencies required for the Arabic language teachers for the fourth grade in the directorate of the southern Ghour from the perspective of teachers themselves as well as the relationship of that with some demographic variables. In order to achieve the study objectives, the researcher developed a questionnaire that consisted of (39) items distributed to six domains; its validity and reliability were verified. The study sample consisted of (47) male and female teachers who were chosen in the simple random way of sampling, from those who teach the subject of Arabic language for the fourth grade. The study results showed that the level of teaching competencies required for the Arabic language teachers for the fourth grade in the directorate of the southern Ghour was high and for all the domains. The domain of (human relationships and classroom management) was in the first place, followed by the domain of (preparation and planning), then the domain of (implementing the lesson), followed by the domain of (evaluation), then the domain of (scientific side and vocational development), and finally the domain of (educational aids and techniques). The results showed that there are no statistically significant differences for the level of teaching competencies required for the Arabic language teachers at the total level and for the domains of ( scientific side and vocational development, implementing the lesson, human relationships and classroom management, ad evaluation) attributed to the variable of years of experience in favor of the (6) years and more. The results also revealed that there are no statistically significant differences at the level ( α≤0.05 ) due to the variables of gender and educational qualification regarding the level of teaching competencies required for the Arabic language teachers for the fourth grade. In the light of the results, the study recommended the necessity of holding more training courses for the male and female teachers of Arabic language in order to enable them to acquire the teaching competencies required for all the educational stages and academic grades.